Distribution patterns, larval growth and hatch dates of early stages of the mote sculpin Normanichthys crockeri (Scorpaeniformes, Normanichthyidae) in the upwelling ecosystem off central Chile - Landaeta,Mauricio F (Universidad de Valparaíso. Facultad de Ciencias del Mar, 2010)
The variability of spatial and temporal distribution of early stages of the mote sculpin Normanichthys crockeri from the upwelling ecosystem off central Chile was examined using a series of six oceanographic cruises, otolith-based larval growth, and experimental trials. Adults spawned year-round in surface waters near capes and inside bays along central Chile, which reduced offshore advection. Egg densities of 16-788 10 m-2 were observed. Small larvae (~2.7 mm body length) hatched after a few days and fed endogenously for 6 days. Pre and postflexion larval N. crockeri were retained over the shelf and near the coast and were vertically located in the mixed layer of the water column (from surface to ~ 50 m depth). No evidence of diel vertical migration was detected in larvae during the austral spring and summer seasons. N. crockeri larvae showed linear growth rates of 0.15-0.20 mm day-1 in the first three months of life during spring and summer. Compared with the reproductive tactics of other small pelagic fishes from the area (Engraulis ringens and Strangomera bentincki), N. crockeri shared the same spawning areas; however larvae showed slower growth rate.